2022
DOI: 10.12659/msm.935711
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Poor Outcomes of Thoracic Ossification of Ligamentum Flavum After Laminectomy

Abstract: Background Thoracic ossification of ligamentum flavum (TOLF) is a common pathological change of the thoracic ligamentum flavum. Identifying the risk factors for poor prognosis is critical for choosing suitable surgical methods. Material/Methods A total of 64 patients with TOLF after laminectomy were reviewed between January 2010 and April 2018 at the Department of Spine Surgery of the Third Hospital of Hebei Medical University. The Japanese Orthopaedic Association (JOA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…Previous retrospective studies on postoperative neurological recovery in TOLF patients have rarely been analyzed concerning follow‐up time 18,24 . Similarly, few studies have focused on the long‐term QoL of TOLF patients after surgery; in a study of long‐term QoL after posterior decompression via an uni‐or bilateral approach in patients with degenerative thoracic spinal stenosis, Siller et al 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous retrospective studies on postoperative neurological recovery in TOLF patients have rarely been analyzed concerning follow‐up time 18,24 . Similarly, few studies have focused on the long‐term QoL of TOLF patients after surgery; in a study of long‐term QoL after posterior decompression via an uni‐or bilateral approach in patients with degenerative thoracic spinal stenosis, Siller et al 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous retrospective studies on postoperative neurological recovery in TOLF patients have rarely been analyzed concerning follow-up time. 18,24 Similarly, few studies have focused on the long-term QoL of TOLF patients after surgery; in a study of long-term QoL after posterior decompression via an uni-or bilateral approach in patients with degenerative thoracic spinal stenosis, Siller et al 25 reported that 645 patients with surgery for degenerative spondylotic myelopathy within 6 years were followed up for an average of 35.1 months and did not suggest that differences in length of follow-up were significantly correlated with QoL. Our study showed that, grouped by a mean follow-up time of 70.8 months, the difference between the relatively longer and relatively shorter follow-up groups was not statistically significant on the EQ-5D-5L value set, and a difference was found only on the EQ-VAS.…”
Section: Follow-up Timementioning
confidence: 99%